Temporary trigeminal ganglion stimulation can improve zoster-related trigeminal neuralgia: a retrospective study in a single center - Kan Yue; Shengrong Xu; Xin Hu; Junhong Li; Ruilin He; Zongbin Jiang (Frontiers in Neurology)
IntroductionConventional management approaches have been challenged in dealing with zoster-related trigeminal neuralgia. Percutaneous trigeminal ganglion stimulation (TGS) has been rarely reported as a potential treatment option for alleviating pain associated with this condition. The present study investigated the application of percutaneous TGS in a series of patients suffering from Zoster-related trigeminal neuralgia to evaluate its potential efficacy of pain relief.MethodsWe retrospectively reviewed the medical records of all patients who underwent TGS at the Department of Pain Management, Second Affiliated Hospital of Guangxi Medical University. All patients were followed for up to 6 months. Clinical data, including the Visual Analog Scale (VAS), Pittsburgh Sleep Quality Index (PSQI), and medication consumption were recorded before and after treatment. Adverse events related to the treatment were also documented.ResultsA total of nine patients underwent percutaneous TGS for Zoster-related trigeminal neuralgia. Among these patients, five (56%) experienced more than 50% pain relief at discharge. At the six-month follow-up, the mean VAS score decreased from preoperative 6.1 ± 1.5 to 2.5 ± 1.9, demonstrating a statistically significant reduction (t = 4.36, p < 0.05). The PSQI also showed a significant reduction from a baseline score of 14.1 to 6.5 at the six-month follow-up (Z = 4.2, p < 0.05). Seven patients reported satisfaction with the treatment and no serious adverse events occurred.DiscussionThe results of the present study suggest that this contributes growing evidence that percutaneous TGS may be an effective treatment for Zoster - related trigeminal neuralgia.